Analysis The Mediating Effect of Guanxi Elements on Social Shopping Intention - Agustina Fitrianingrum; Regita Helmiani Harahap (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Recently, the growth of social media has driven the development of social commerce (s-commerce). The purpose of this study is to investigate consumer decisions in s-commerce, where this research conducts empirical research on social media to validate how guanxi elements (eg ganqing, renqing and xinren) affect consumer decisions in s-commerce. In the research model, the researcher conducted an online survey to collect data. Respondents for this study were ethnic Chinese students in Batam. The sample size is 279 responses. The data is analyzed using partial least square (PLS)—a structural equation modelling (SEM) technique. This thesis confirm that all hypothesis have significant relationship and positively related to Social Shopping Intention.